2012
DOI: 10.1590/s1516-31802012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes in a patient with Ellis-van Creveld syndrome

Abstract: CONTEXT: Ellis-van Creveld (EVC) syndrome is a rare autosomal recessive disease characterized by disproportionate short stature, narrow thorax, postaxial polydactyly, nail and tooth abnormalities and congenital heart disease. CASE REPORT: The patient was a 22-year-old Caucasian man, the third child of consanguineous parents. He received the diagnosis of insulin-dependent diabetes mellitus (DM) at 16 years of age, and around one year later, he underwent surgery to correct a partial atrioventricular septal defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…10 Graziadio et al reported about a patient with EVC syndrome who was 22 years old and had Type-1 diabetes. 11 While cases of EVC syndrome have been reported from India, no case with survival into late adulthood has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…10 Graziadio et al reported about a patient with EVC syndrome who was 22 years old and had Type-1 diabetes. 11 While cases of EVC syndrome have been reported from India, no case with survival into late adulthood has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Graziadio et al reported about a patient with EVC syndrome who was 22 years old and had Type-1 diabetes. [11] While cases of EVC syndrome have been reported from India, no case with survival into late adulthood has been reported so far. EVC needs to be distinguished from a number of closely related entities.…”
Section: Fig 5: Echo Picture Showing Common Atrium and Pericardial Ementioning
confidence: 99%
“…1,2 El fenotipo es variable y afecta múltiples órga-nos. Sus características clínicas se describieron en numerosos informes [3][4][5][6] y series de casos. [7][8][9][10][11][12] Después del nacimiento, el cuadro clínico suele ser la tétrada conformada por: 1) estatura pequeña con acortamiento de la parte distal de los miembros y acortamiento de las falanges media y distal; 2) polidactilia en las manos (casi siempre bilateral), que ocasionalmente afecta los pies; 3) displasia condroectodérmica que afecta principalmente las uñas, el cabello y los dientes, y 4) malformaciones cardíacas congénitas (50% a 60% de los casos); las más frecuentes son defectos septales y aurícula única; también se han informado defectos de las válvulas mitral y tricúspide, persistencia del conducto arterioso y síndrome del corazón izquierdo hipoplásico.…”
Section: Introductionunclassified